Are blastocyst aneuploidy rates different between fertile and infertile populations? - Kort, Jonathan D. (J Assist Reprod Genet, 2017)
PURPOSE: This study aimed to determine if patients with infertility or recurrent pregnancy loss have higher rates of embryo aneuploidy than fertile controls. METHODS: This was a retrospective review of all pre-implantation genetic screening (PGS) cases processed by a single reference lab prior to March 2014 after a blastocyst biopsy. Cases were excluded if no indication for PGS was designated or patients were translocation carriers. The fertile control group consisted of patients undergoing IVF with PGS for sex selection only. The comparison cohorts included those with recurrent pregnancy loss, male factor infertility, unexplained infertility, prior failed IVF, or previous aneuploid conceptions. A quasi-binomial regression model was used to assess the relationship between the dependent variable, aneuploidy rate and the independent variables, maternal age and reason for PGS. A quasi-Poisson regression model was used to evaluate the relationship between similar independent variables and the number of blastocyst biopsies per case. RESULTS: The initial study population consisted of 3378 IVF-PGS cycles and 18,387 analyzed trophectoderm samples. Controlling for maternal age, we observed an increased rate of aneuploidy among patients with recurrent pregnancy loss (OR 1.330, p < 0.001), prior aneuploid pregnancy (OR 1.439, p < 0.001), or previous failed IVF cycles (OR 1.356, p = 0.0012) compared to fertile controls. Patients with unexplained and male factor infertility did not have a significantly different aneuploidy rate than controls (p > 0.05). The increase in aneuploidy in patients with RPL and prior IVF failure was driven by both an increase in meiotic (OR 1.488 and 1.508, p < 0.05) and mitotic errors (1.269 and 1.393, p < 0.05) relative to fertile controls, while patients with prior aneuploid pregnancies had only an increased risk of meiotic error aneuploidies (OR 1.650, p < 0.05). CONCLUSIONS: Patients with recurrent pregnancy loss, previous IVF failures, and prior aneuploid pregnancies have a significantly higher, age-independent, aneuploidy rate compared to patients without infertility.